The implementation of songs in teaching listening for young learners in online learning environment - Diana Paskalisa; Irma Savitri Sadikin (Indonesian Institute for Counseling, Education and Therapy (IICET), 2022)
There are currently a variety of technologically-based techniques for creating an attractive English-learning environment for young learners. Using songs as an engaging technique in audiovisual offers meaningful sources of interesting and relevant listening materials. This study investigates what learning principles young learners observe in songs and how they respond to songs during the online learning experience. Twelve students were included in a case study at a private elementary school in Jakarta. This study revealed that the materials presented in songs and videos align with the learning principles of young learners, such as they have short attention and are easy to distract, they can gain understanding from direct experience through objects and visual aids, they are enthusiastic and positive about learning, and they are being responsive to the instruction. These findings contribute to facilitating a more creative learning environment. Students generally responded positively by intimately watching videos and participating in activities. They enjoyed learning English through songs. Therefore, songs are recommended in EFL classrooms as supplementary activities or at home for self-study.